Barriers to, and facilitators in, introducing integrated diabetes care in Ireland: a qualitative study of views in general practice. Issue 8 (19th August 2013) - Mc Hugh, Sheena; O'Mullane, Monica; Perry, Ivan J; Bradley, Colin
Abstract : Objective: To examine the barriers to, and facilitators in, improving diabetes management from the general practice perspective, in advance of the implementation of an integrated model of care in Ireland. Design: Qualitative using semistructured interviews. Setting: Primary care in the Republic of Ireland. Participants: Purposive sample of 29 general practitioners (GPs) and two practice nurses. Methods: Data were analysed using a framework approach. Results: The main barriers and facilitators occurred at the level of the health system but had a ripple effect at an organisational, professional and patient level. The lack of targeted remuneration for diabetes management in the Irish health system created apathy in general practice and was perceived to be indicative of the lack of value placed on chronic disease management in the health system. There were 'pockets of interest' among GPs motivated by 'vocational' incentives such as a sense of professional duty; however, this was not sufficient to drive widespread improvement. The hospital service was seen as an essential support for primary care management, although some participants referred to emerging tension between settings. The lack of coordination at the primary–secondary interface resulted in avoidable duplication and an 'in the meantime' period of uncertainty around when patients would be called or recalled by specialist services. Facilitators included the availability of nursing support and serendipitous access to services. The lack of resources in the community was considered to be at odds with policy to shift routine management to general practice, which is fast reaching saturation. Conclusions: At present, intrinsic motivation is driving the improvement of diabetes care in Ireland. This will not be sufficient to implement the proposed reform including a national model of integrated care. Policymakers need to assess and prepare for the disparate levels of interest and infrastructure in primary care in Ireland to support this change.